Assessment of the Impact of State Regulation of Retail Trade Networks Development on the Wholesale Sector - CHEGLOV, V.P.; MKHITARYAN, S.V.; DANCHENOK, L.A.; RYKALINA, O.V.; TULTAEV, T.A. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).10, 2020)
The article is dealing with the issues of state regulation of the consumer market, where the interests of producers, wholesale intermediaries, and retail trade are traditionally encountered. The authors consider the features of state regulation of the formation and development processes of multi-object and omnichannel trading systems in Russia in the context of the country's entry into the global economy, the opening of the domestic market for foreign business structures, and commodity imports in a situation with a small business that is not fully established. The results of the conducted study complement the experience of the international community in regulating system formation in trade. The article analyzes significant differences in the state intervention mechanisms in the economic relations of retail chains and their suppliers, as well as the impact of stricter legislation on wholesale trade, and its place and role in the commodity distribution system. The authors prove that excessive regulation of the retail market causes negative consequences in its adjacent segments, justify the upcoming redistribution of the market between large retail chains and specialized wholesale companies in favor of the former ones, show the development prospects of the distribution, and the impact of this process on small retail businesses, as well as formulate proposals for optimizing approaches to regulating the transformation of the trade sector in the transition economy.